2008
DOI: 10.1073/pnas.0709741105
|View full text |Cite|
|
Sign up to set email alerts
|

The globular tail domain puts on the brake to stop the ATPase cycle of myosin Va

Abstract: Myosin Va is a well known processive motor involved in transport of organelles. A tail-inhibition model is generally accepted for the regulation of myosin Va: inhibited myosin Va is in a folded conformation such that the tail domain interacts with and inhibits myosin Va motor activity. Recent studies indicate that it is the C-terminal globular tail domain (GTD) that directly inhibits the motor activity of myosin Va. In the present study, we identified a conserved acidic residue in the motor domain (Asp-136) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(117 citation statements)
references
References 37 publications
4
109
0
1
Order By: Relevance
“…Conserved basic residues (K1706 and K1779) found on the tip of the SD-2 H7-H8 loop and H11 helices are essential for this regulation (21). Whereas this region is conserved in vertebrate Myo5 and yeast Myo2p, it is not in Myo4p (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conserved basic residues (K1706 and K1779) found on the tip of the SD-2 H7-H8 loop and H11 helices are essential for this regulation (21). Whereas this region is conserved in vertebrate Myo5 and yeast Myo2p, it is not in Myo4p (18).…”
Section: Resultsmentioning
confidence: 99%
“…Mutational analysis has shown that the SD-2 tip of the GTD interacts with the motor domain in the folded inhibited state (21). The general topology of the folded Myo5 conformation indicates that the SD-1 tips of the two GTDs in the folded Myo5 dimer might interact with each other and with the stalk.…”
Section: Structural Recognition Of the Mlph By An Isoform-specific Bimentioning
confidence: 99%
“…The existence of the folded inhibited state of mammalian myosin V is supported by sedimentation analysis (Krementsov et al, 2004;Li et al, 2004;Wang et al, 2004), cryoelectron microscopy reconstruction (Liu et al, 2006;Thirumurugan et al, 2006), and ATPase activity assays (Li et al, 2008). Activation of the motor occurs after cargo receptor binding for MyoVa in vitro (Li et al, 2005;Sckolnick et al, 2013), as is the case for yeast myosin V in vivo (Donovan and Bretscher, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…The recombinant baculovirus encoding the cDNA of Myo5 heavy chain was prepared as described previously (7,24). To prepare Myo5 proteins, Sf9 cells were co-infected with the recombinant baculovirus encoding Myo5 heavy chain and that encoding CaM and purified as described previously (7,24). The concentrationsofthepurifiedproteinsweredeterminedbyabsorbance at 280 nm using the following molar extinction coeffi- , Myo5c(5aIQ1)-HMM.…”
Section: Methodsmentioning
confidence: 99%
“…The GTD interacts with different cargo-binding proteins through distinct binding sites located on the surface of both subdomain I and II (12, 14, 15, 18 -20). On the other hand, bioinformatic analysis and biochemical characterization suggest that the head-binding site is located in subdomain II (7,12,22).…”
mentioning
confidence: 99%